Impact of inorganic buffering ions on the stability of Fe(vi) in aqueous solution: role of the carbonate ion. Issue 6 (21st January 2016) - Kolář, Michal; Novák, Petr; Šišková, Karolína M.; Machala, Libor; Malina, Ondřej; Tuček, Jiří; Sharma, Virender K.; Zbořil, Radek
Abstract : The study presents a systematic kinetics investigation of the decay of ferrate(vi ) in the presence of inorganic buffering ions (borate, phosphate, and carbonate) at a pH range from 6.0 to 9.0. Abstract : An iron compound of +6 oxidation state (Fe VI O4 2−, Fe(vi )) is a green molecule for various applications (water oxidation catalyst, organic transformation for synthesis, and water remediation agent). However, its use is hindered because of its inherent decay in aqueous solution. This study presents a systematic kinetics investigation of the decay of ferrate(vi ) in the presence of inorganic buffering ions (borate, phosphate, and carbonate) at a pH range from 6.0 to 9.0. When the heterogeneous decay of Fe(vi ) on ferric products was inhibited by phosphate, detailed kinetic analysis revealed that the carbonate anion enhanced the Fe(vi ) decay rate, compared to phosphate and borate ions. The order of the Fe(vi ) decay rate under neutral solution conditions was carbonate > phosphate ≥ borate. In alkaline solution, the decay rates of Fe(vi ) were similar for the studied buffering ions. The decay of Fe(vi ) in the presence of the carbonate ion was described by mixed first- and second-order kinetics and the first-order rate constant ( k 1 ′) had a linear relationship with the concentration of the carbonate ion at a neutral pH ( k 1 ′ = 0.023 + 3.54 × [carbonate] L mol −1 s −1 ). The analysis of the Fe(vi ) decay intermediates/products (˙O2 −, H2 O2, and O2 ) suggests similar decay pathways in the presence of different buffering anions. The impact of carbonate ions on the size of the nanoparticles of the Fe(iii ) precipitate, the final reduced form of Fe(vi ), was studied using transmission electron microscopy, 57 Fe Mössbauer spectroscopy, and magnetization measurements. The results indicated that carbonate ions induce the formation of ultrasmall iron(iii ) oxyhydroxide nanoparticles (<5 nm), which apparently contribute to increased decay of Fe(vi ) due to their larger specific surface area. The described homogeneous reaction of carbonate with Fe(vi ) has important implications in the efficiency of environmental Fe(vi ) applications. On the other hand, the observed low reactivity of borate with Fe(vi ) demonstrates that borate is the least reactive buffer in studies of Fe(vi ) reactivity in neutral solutions.